Physiology and clinical role of salusin-? and salusin-? peptides in the cardiovascular system: Review - Aydin, Suna; Eren, Mehmet Nesimi; Aydin, Süleyman (Turkiye Klinikleri, 2014)
Hypertension and atherosclerosis are the major cause of cardiovascular diseases and the leading cause of death globally. Some peptide hormones play key roles in the regulation of the pathogenesis of hypertension and atherosclerosis. In this sense, salusin-? (28 amino acids) and ? (20 amino acids) are two new important peptides that cause strong hypotension and bradycardia. Both peptides are broadly expressed in kidneys, blood vessels, hypothalamus, pituitary gland, (hypophysis) and human coronary atherosclerotic plaques, with dominance of salusin-? in macrophage foam cells, fibroblasts, and vascular smooth muscle cells (VSMCs), where it exerts different functions. Indeed, salusin-? had a role macrophage foam cell formation in the human, albeit salusin-? had not. Both salusin-? and salusin-? improved calcium uptake and protein synthesis in neonatal rat cardiomyocytes through the calcineurin, calcium, microtubule-associated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) and protein kinase C (PKC) signal pathways. As stated above, both salusin-? and -? were multifunctional bioactive peptide hormones, and both of them play a pivotal role in the maintenance of blood pressure homeostasis and the pathogenesis of atherosclerosis. Therefore this review focuses on role of salusin peptides in the cardiovascular system as they play a major role in regulating blood pressure and the pathogenesis of atherosclerosis. Copyright © 2014 by Türkiye Klinikleri.
Kardiyovasküler sistemde salusin-? ve salusin-?'ni{dotless} n fizyolojisi ve klinik rolü
Keywords: Atherosclerosis; Hypertension; Salusin-? human; Salusin-? human